Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
tamanh nguyen

\(\dfrac{1}{\sqrt{6}-2}+\dfrac{1}{\sqrt{6}+2}\)

nthv_.
28 tháng 10 2021 lúc 20:37

\(\dfrac{\sqrt{6}+2}{6-4}+\dfrac{\sqrt{6}-2}{6-4}=\dfrac{2\sqrt{6}}{6-4}=\sqrt{6}\)

gấu béo
28 tháng 10 2021 lúc 20:40

⇔ \(\dfrac{\left(\sqrt{6}+2\right)+\left(\sqrt{6}-2\right)}{\left(\sqrt{6}-2\right)\left(\sqrt{6}+2\right)}\)

⇔ \(\dfrac{\sqrt{6}+2+\sqrt{6}-2}{2}=\dfrac{2\sqrt{6}}{2}=\sqrt{6}\)

Dũng
28 tháng 10 2021 lúc 20:40

=1(√6 + 2) + 1(√6 -2)/6-4

=√6 + 2 + √6 - 2/2

=2√6/2

=√6

/:là phân số nhé :')


Các câu hỏi tương tự
Nguyên Phan
Xem chi tiết
Yết Thiên
Xem chi tiết
Ly Ly
Xem chi tiết
Super Vegeta
Xem chi tiết
Gia Bảo Hà Đình
Xem chi tiết
phan anh thư
Xem chi tiết
Yết Thiên
Xem chi tiết
Nguyễn Đan Xuân Nghi
Xem chi tiết
Ly Ly
Xem chi tiết
nood
Xem chi tiết